2004
DOI: 10.4319/lo.2004.49.2.0376
|View full text |Cite
|
Sign up to set email alerts
|

Submarine groundwater discharge of nutrients and copper to an urban subestuary of Chesapeake Bay (Elizabeth River)

Abstract: We investigated the role submarine groundwater discharge (SGD) plays in the delivery of nutrients and copper to the Elizabeth River (Virginia) estuary, a major subestuary of lower Chesapeake Bay. Using an approach based on radium isotopes, we concluded that two distinct sources of groundwater were equally impacting the estuary: a surface (marsh) aquifer and deep aquifer source each with a unique 228 Ra/ 226 Ra activity ratio. Considering each of these sources, we calculated an SGD flux of 1 ϫ 10 6 m 3 d Ϫ1 (Ϯ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(61 citation statements)
references
References 32 publications
7
53
0
1
Order By: Relevance
“…Nitrate concentrations ranged from 0.5 M at station A to 331 M at station D, indicating a pronounced nitrate gradient across the study site (Table 1). Ammonium concentrations ranged from a low of 9.2 M at station A to a maximum of 160 M at station C. Although the ammonium concentrations were high compared to those in typical estuarine and marine water columns, they are not atypical of porewaters (8,11,17), which have reported concentrations in excess of 1 mM. Salinity increased in the cross-shore direction as nutrient concentrations decreased and ranged from 8 practical salinity units (psu) at station E to 33 psu at station A.…”
Section: Resultsmentioning
confidence: 92%
“…Nitrate concentrations ranged from 0.5 M at station A to 331 M at station D, indicating a pronounced nitrate gradient across the study site (Table 1). Ammonium concentrations ranged from a low of 9.2 M at station A to a maximum of 160 M at station C. Although the ammonium concentrations were high compared to those in typical estuarine and marine water columns, they are not atypical of porewaters (8,11,17), which have reported concentrations in excess of 1 mM. Salinity increased in the cross-shore direction as nutrient concentrations decreased and ranged from 8 practical salinity units (psu) at station E to 33 psu at station A.…”
Section: Resultsmentioning
confidence: 92%
“…Again, the mobilization of these metals in groundwater was attributed to the Fe and Mn redox cycles and the suspected low pH of the groundwater as it passed through the sediment deposits left behind from mining activities. Charette and Buesseler [2004] studied copper (Cu) fluxes in SGD near a naval base on the eastern coast of the United States, but found that this source was minor compared to that from Cu-based antifouling paints used on boat hulls. Beck et al [2009] compared SGD-derived metal inputs to those from treated wastewater inputs to a surface estuary near New York City.…”
mentioning
confidence: 99%
“…However, the use of multiple tracers should alleviate many of the complexities associated with assessing groundwater in the system. Many studies have utilized natural geochemical tracers to quantify groundwater in coastal systems [Cable et al, 1996a;Moore, 1998;Corbett et al, 2000;Top et al, 2001;Charette and Buesseler, 2004], which are found in elevated concentrations relative to surface waters [Davis et al, 1980]. This study incorporates 222 Rn and 4 He/ 3 He/ 3 H as natural tracers of groundwater.…”
mentioning
confidence: 99%